2016
DOI: 10.1080/09638288.2016.1198429
|View full text |Cite
|
Sign up to set email alerts
|

Walking activity during daily living in children with myelomeningocele

Abstract: Purpose To quantify the walking activity of children with myelomeningocele during daily living. Method Walking activity was measured using a StepWatch activity monitor over one week in 47 children with myelomeningocele (27 males; 9y 11mo SD 2y 7mo; 18 sacral, 9 low lumbar, 20 mid-high lumbar) and 7 children with typical development (5 males; 11y 1mo SD 1y 11mo) in a prospective, cross-sectional study. Average total steps per day, number of steps and minutes spent at low, medium and high intensity stepping we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
1
6
0
2
Order By: Relevance
“…This group also exhibited typical numbers of daily loading cycles (steps per day). The daily steps recorded on activity monitors worn by participants with spina bifida (9656 [SD 3095] steps) were comparable to those previously reported from 7 children with typical development who underwent the same activity monitoring protocol (9589 [SD 3322] steps [34]). Our findings of near-typical joint forces and loading cycles, combined with the neartypical bone health observed (Table 1), suggest that maintaining ambulation and muscle strength can promote bone health in this group.…”
Section: Tibial Forces and Bone Healthsupporting
confidence: 74%
“…This group also exhibited typical numbers of daily loading cycles (steps per day). The daily steps recorded on activity monitors worn by participants with spina bifida (9656 [SD 3095] steps) were comparable to those previously reported from 7 children with typical development who underwent the same activity monitoring protocol (9589 [SD 3322] steps [34]). Our findings of near-typical joint forces and loading cycles, combined with the neartypical bone health observed (Table 1), suggest that maintaining ambulation and muscle strength can promote bone health in this group.…”
Section: Tibial Forces and Bone Healthsupporting
confidence: 74%
“…The study showed that children with sacral and low lumbar level lesions (based on IMSG rating) function similarly to their typically developing peers, whereas those with mid-high lumbar lesions were less active. [22] The current study expands on the previous work by examining relationships among various classifications of neurosegmental and functional level, and their associations with actual ambulatory activity performance.…”
Section: Discussionmentioning
confidence: 80%
“…This suggests that the type of gait also likely contributes to shape differences. While children with sacral and low lumbar MM (higher functional level of MM) take a similar number of steps per day as TD children, and with a similar profile of low, medium, and high intensity walking [28], previous studies have found that children with all levels of MM exhibit kinematic [29,30,31] and kinetic [32] gait deviations compared to TD children. This suggests that for independently ambulatory children with MM, kinematic (and kinetic) deviations play a significant role in bone remodeling.…”
Section: Discussionmentioning
confidence: 94%